Perception of dental erosion and consumption of carbonated beverages in basketball players aged 15 to 25 at the Municipal Sports Unit of Pachuca de Soto, Hidalgo. - Acosta Romero , Karime; Bautista Robledo, Anylú; Elizalde Fernández, Fernanda; Serratos Aguilar, Ana A.; Monjarás Ávila, Ana J. (Educación y Salud Boletín Científico Instituto de Ciencias de la Salud Universidad Autónoma del Estado de Hidalgo, 2022)
Dental erosion is the progressive and irreversible loss of dental structure associated with the action of chemicals in which bacteria do not intervene. This cross-sectional study was carried out in 100 young basketball players of the Unidad Deportiva de Pachuca de Soto, Hidalgo. The objective was to relate the consumption of carbonated beverages and dental erosion. The measurement was carried out with the Eccles and Jenkins index. The 47 % of players presented dental erosion. It was shown that basketball players who frequently consumed carbonated beverages presented dental erosion in comparison with those who did not consume them.